(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
This is an essay of hope in humanity’s moral and intellectual capacity to envision, jointly plan, and carry-forth a concerted effort to meet the historically unique challenges we face and also to create opportunities for fulfilling the potential of our evolutionary heritage. It assumes that to achieve the above, it is imperative to strengthen the effectiveness of education, training and information sharing guided by common values and principles that buttress and foster ways of living in an integrally peaceful way. This will entail protecting and promoting fundamental human rights and freedoms, particularly the Right to Education.